2016
DOI: 10.1134/s1066362216010070
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of americium and europium with functionalized calixarenes from alkaline solutions

Abstract: Extraction of 241 Am and 152 Eu from alkaline carbonate solutions with solutions of functionalized calix[4]arenes and their nonmacrocyclic analogs in m-nitrobenzotrifluoride was studied. The dependence of the distribution ratios and separation factors of the radionuclides on pH of the aqueous phase in the interval from 9.8 to 13.5 and on the position and electronic nature of functional groups (alkyl, pyridine, phosphoryl) in the calixarene core was examined. The composition of the extractable solvates of ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It is acknowledged that solvent extraction is a significant part of the process . Due to the importance of solvent extraction in separating europium and its similar ions, numerous studies in the literature have been conducted to investigate the effect of different solvents on the removal of this element. Studies by Tunsu and co-workers showed that the separation of yttrium and europium ions could be provided by Cyanex572. The increase in temperature has adverse effects on the separation process, and the high hydrochloric acid concentration (>3 mol/L) is required for the stripping and recovery of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…It is acknowledged that solvent extraction is a significant part of the process . Due to the importance of solvent extraction in separating europium and its similar ions, numerous studies in the literature have been conducted to investigate the effect of different solvents on the removal of this element. Studies by Tunsu and co-workers showed that the separation of yttrium and europium ions could be provided by Cyanex572. The increase in temperature has adverse effects on the separation process, and the high hydrochloric acid concentration (>3 mol/L) is required for the stripping and recovery of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…Another consideration is the ability to form soluble complexes under the prevailing alkaline conditions. In the literature, various ligand derivatives, such as alkyl(aminomethyl) phenols, [5] calix [4]arenes, [6][7] thiacalix, [8] and alkylpyrocathecols, [9][10] have been applied for the extraction of f-elements from high pH, with alkylpyrocathecols showing Am[III] extraction as high as 97% from 6 M NaOH. Several sulfonamide-based ligands have been synthesized by our group aiming at f-element extraction from alkaline solutions, and have yielded promising results for Sm(III) extraction, which was used as a surrogate for Am(III).…”
Section: Introductionmentioning
confidence: 99%
“…The isotope 90 Sr is among the most dangerous radionuclides, as it can accumulate in bone tissue on a par with calcium and lead to radiation damage of surrounding tissues. Therefore, an important goal is to develop an effective method for the extraction of strontium from high-level waste.…”
mentioning
confidence: 99%
“…This method can be used for the extraction of the long-lived radioactive strontium isotope 90 Sr from high-level waste, as well as for the separation of parent 90 Sr and its daughter isotope 90 Y (used in radiation therapy). However, the authors of [80] did not present distribution ratios or separation factor which are the key characteristics of extraction processes.…”
mentioning
confidence: 99%